PENGARUH PENGARUH MOTIVASI KERJA DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA KARYAWAN (Studi Kasus Karyawan Bagian SDM PT. Perkebunan Nusantara V Pekanbaru) - Sirait, Rika Lisandy; Sidiq, Kasmiruddin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Work Motivation and Career Development Are Very Influential on Job Satisfaction. Because these goals together provide support and encouragement to improve employee career capabilities, so that employees are passionate about increasing education levels so that there is satisfaction in working. This study aims to determine the Effect of Work Motivation and Career Development on Job Satisfaction (Case Study of Employees in the HR Section of PT Perkebunan Nusantara V Pekanbaru). Where two independent variables are proposed namely Work Motivation and Career Development and one dependent variable is employee Job Satisfaction. This research was conducted at the head office of PT Perkebunan Nusantara V Pekanbaru, located on Jalan Rambutan No. 43, Kota Pekanbaru, Riau. In this study the method used is descriptive and quantitative with the SPSS program. This research sample was taken as many as 35 respondents with the census method. Data obtained from the results of the questionnaire and subsequently obtained were then tested with statistics through the SPSS program. From data analysis which includes test validity, reliability, simple linear regression and multiple linear regression. Tests conducted show that work motivation has a positive and significant effect on job satisfaction, work motivation has a positive and significant effect on job satisfaction, then work motivation and career development have a positive and significant effect on job satisfaction of HR employees of PT Perkebunan Nusantara V Pekanbaru. Keywords: Work Motivation, Career Development, Job Satisfaction.